Green Innovation and Islamic Boarding School Financial Performance: a Case Study in Pondok Pesantren Tahfiz Al-Quran (PPTQ) Al Munawaroh - M. Nasyah Agus Saputra; Kurnia Cahya Lestari; Muhammad Ala'uddin; Moh. Ya’qub; Fri Haendid Alfiyan (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2024)
Abstract: The purpose of this study is to determine the dynamics of the relationship between green innovation and financial performance of Pondok Pesantren Tahfidzul Quran (PPTQ) Al-Munawaroh. More specifically, this study examines how green innovation practices which include products, processes, and organizations contribute to improving the financial performance of PPTQ Al-Munawaroh. This research uses a qualitative case study approach collected through face-to-face interviews, observation and documentary analysis. The results showed that the green innovation practice mechanism at PPTQ Al-Munawaroh has been running well and developed to change the habits of boarding school residents to care about the environment. The findings indicate that green innovation practices at PPTQ Al-Munawaroh contribute to financial improvement through resource efficiency, especially in operational savings and economic benefits. Keywords: Green Innovation; Financial Performance; Islamic Boarding School; SDGs. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui dinamika hubungan green innovation dan kinerja keuangan Pondok Pesantren Tahfidzul Quran (PPTQ) Al-Munawaroh. Lebih spesifik, penelitian ini mengkaji bagaimana praktik green innovation yang meliputi produk, proses, dan organisasi berkontribusi dalam meningkatkan kinerja keuangan PPTQ Al-Munawaroh. Penelitian ini menggunakan pendekatan studi kasus kualitatif yang dikumpulkan melalui wawancara tatap muka, observasi dan analisis dokumenter. Hasil penelitian menunjukkan bahwa mekanisme praktik green innovation di PPTQ Al-Munawaroh telah berjalan dengan baik dan dikembangkan untuk mengubah kebiasaan warga pondok Pesantren untuk peduli pada lingkungan. Temuan menunjukkan bahwa praktik inovasi ramah lingkungan di PPTQ Al-Munawaroh berkontribusi terhadap peningkatan keuangan melalui efisiensi sumber daya, terutama dalam penghematan operasional dan manfaat ekonomi. Kata Kunci: Green Innovation; Kinerja Keuangan; Pondok Pesantren; SDGs.